HUBUNGAN KEPATUHAN PERAWAT MELAKUKAN HAND HYGIENE TERHADAP KEJADIAN PLEBITIS DI RUANG PERAWATAN INTERNA RS PELAMONIA MAKASSAR - Nusdin Nusdin (Yayasan Akrab Pekanbaru, 2018)
Phlebitis is venous inflamasi caused by the contamination of microorganism. The purpose of this study is to determine the relation of nurses to do hand hygiene on plebitis occurrence in internal treatment room of Pelamonia Hospital Makassar. The sample of this research is 35 respondents. The research design uses Analytical Survey research type using Cross Sectional approach. The result of research based on Chi Square test p value = 0,001 (p <0,05. The conclusion of this research indicate that there is relation of nurse to do hand hygiene to plebitis incident in internal treatment room of Pelamonia Hospital Makassar. Suggestions To improve the prevention and control of nosocomial infections in the internal treatment room of Pelamonia Hospital Makassar it is suggested to further optimize adherence and maintain compliance in hand hygiene by means of six steps and used in five time (five moments). Keyword: Obedience, Hand Hygiene, Phlebitis.